2019
DOI: 10.1002/1878-0261.12520
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of DDR1 with antibody‐drug conjugates has antitumor effects in a mouse model of colon carcinoma

Abstract: DDR1 has been identified as a cancer‐associated receptor tyrosine kinase that is highly expressed in several malignancies relative to normal tissues. Clinically approved multi‐kinase inhibitors, such as nilotinib, inhibit DDR1‐mediated tumor growth in xenograft models, suggesting DDR1 might be a potential target for cancer treatments. Here, we employed an antibody‐based strategy with a novel anti‐DDR1 antibody‐drug conjugate (ADC) for colon carcinoma treatment. We developed T 4 H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 56 publications
2
18
0
Order By: Relevance
“…Finally, DDR1 inhibition displays antitumor activity in mice that have already developed DDR1dependent metastatic nodules, revealing an additional important DDR1 role in metastatic growth (42). Consistently, DDR1 expression level is associated with shorter overall survival in patients with mCRC, and DDR1 phosphorylation is strongly increased in the corresponding metastatic lesions (42,43). Interestingly, DDR1 upregulation is an independent marker of poor prognosis in patients with stage IV CRC, and is not correlated with any CMS subtype (42).…”
Section: Ddr1 In Crc Metastasesmentioning
confidence: 86%
See 1 more Smart Citation
“…Finally, DDR1 inhibition displays antitumor activity in mice that have already developed DDR1dependent metastatic nodules, revealing an additional important DDR1 role in metastatic growth (42). Consistently, DDR1 expression level is associated with shorter overall survival in patients with mCRC, and DDR1 phosphorylation is strongly increased in the corresponding metastatic lesions (42,43). Interestingly, DDR1 upregulation is an independent marker of poor prognosis in patients with stage IV CRC, and is not correlated with any CMS subtype (42).…”
Section: Ddr1 In Crc Metastasesmentioning
confidence: 86%
“…Due to DDR1 aberrant expression in CRC, an anti-DDR1 antibody-drug conjugate was recently developed for CRC treatment. This agent displayed significant anti-tumor activity in a preclinical model of CRC, without overt toxicity in control animals ( Table 1) (43). Finally, small-molecule allosteric inhibitors of DDR2 extracellular domain inhibit the tumormicroenvironment interaction and breast tumor invasion (70).…”
Section: Targeting Ddr Tumor Activity In Metastatic Crcmentioning
confidence: 99%
“…For instance, DDR1 mAb 48B3 can prevent the invasion and adhesion of G140 human glioma cells 67 . In 2019, Tao et al 68 developed a DDR1 antibody DM4 (an anti–tubulin agent blocking cell division) drug conjugate called T4H11‐DM4, which can suppress colon cancer tumorigenesis in vitro and in vivo.…”
Section: Discoidin Domain Receptor Inhibitorsmentioning
confidence: 99%
“…However, other studies have demonstrated that, in breast carcinomas, DDR1 promotes apoptosis through induction of pro-apoptotic protein BIK1 (Assent et al, 2015;Saby et al, 2018Saby et al, , 2019. In the case of CRC, recent studies have shown that nilotinib, a specific inhibitor of DDR1 phosphorylation, strongly reduced DDR1-mediated CRC cell invasion and metastasis in mouse models (Jeitany et al, 2018), and that the use of antibodydrug conjugates targeting DDR1 exhibits antitumor effects in a mouse model of CRC (Tao et al, 2019). These works have been carried out on CRC cells harboring invasive-like phenotype.…”
Section: Introductionmentioning
confidence: 99%